2019
DOI: 10.1149/2.0841914jes
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of SPS Concentration by the Ring Current Using a Rotating Ring-Disk Electrode with Dissolving Disk Copper to Refresh a Void Free Solution

Abstract: We have devised a new method of monitoring using a rotating ring-disk electrode (RRDE) with dissolving disk copper during copper electrodeposition process. The ring current shows linear relationship with SPS concentration from 0 to 3.5 ppm. To minimize the effects of other additives on ring current monitoring, we have conducted cyclic voltammetry stripping (CVS) to estimate the amount of polyethylene glycol (PEG) and sulfonated diallyl dimethyl ammonium chloride copolymer (SDDACC), the leveler. Through silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The ring potential is kept constant at 0.6 V to oxidize all Cu(I)complexes to Cu 2+ and the transferred electrons are counted as the ring current. 12 However, with the addition of 3 and 5 ppm of 2M5S, the ring current shows detectable decreases while the disk current remains the same. Hence, 2M5S must interact with the Cu(I) complexes to form Cu(I)-2M5S complex, the reactions can be written as follows:…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The ring potential is kept constant at 0.6 V to oxidize all Cu(I)complexes to Cu 2+ and the transferred electrons are counted as the ring current. 12 However, with the addition of 3 and 5 ppm of 2M5S, the ring current shows detectable decreases while the disk current remains the same. Hence, 2M5S must interact with the Cu(I) complexes to form Cu(I)-2M5S complex, the reactions can be written as follows:…”
Section: Resultsmentioning
confidence: 96%
“…2M5S contains a thiol group and thought to form an analogous complex as Cu(I)thiolate. Moreover, 2M5S also contains the δpolarized Nitrogen atoms, then the bonding strength of Cu(I)−2M5S complex is stronger than Cu(I)thiolate complex 12 and not be oxidized at the ring electrode. That is the reason why the ring current decreases with the addition of 2M5S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study develops a highly sensitive sensor for the detection of organic additives to allow the detection of organic additives for plating production lines. Currently, cyclic voltammetric stripping (CVS) is s used to measure the oxidation peak of copper indirectly to detect the concentration of organic additives [16][17]. Xie et al [18] used CVS with a microelectrode and found that the microelectrode can replace a traditional rotating electrode to monitor the concentration of copper ions and organic additives in metal plating solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the acceleration mechanism was investigated by cyclic voltammetry combined with rotating ring-disk electrode (RRDE). 17 Finally, the filling performances of the two model additives were examined by microvia filling experiments.…”
mentioning
confidence: 99%